Enhancing Sustainable Safety Performance in the Construction Industry: A Total Safety Management Approach - Rita Ambarwati; Handaru A. Putra; Dedy Dedy; Wiwik Sulistiyowati; Boy Isma Putra (Binus Business Review, 2025)
Indonesia’s construction industry is known for high accident rates, underscoring the urgency and practical impact of the research. The research explored the causal relationship between Total Safety Management (TSM), safety culture, safety behavior, and safety performance within Indonesia’s construction sector, aiming to reduce high workplace accident rates. The research uniquely integrated these variables into a unified model tailored specifically to the Indonesian construction context, clearly distinguishing itself from previous research by addressing existing gaps in the literature. Data were collected from 173 staff and managers at contractor companies involved in various construction projects, each respondent having at least one year of relevant industry experience. A structured questionnaire assessed the implementation of safety programs and practices in respondents’ workplaces over a three-month period (March to May 2023). Structural Equation Modeling–Partial Least Squares (SEM-PLS) was employed for rigorous data analysis. Findings indicate that TSM significantly influences both safety culture and safety behavior, with each positively impacting overall safety performance. Specifically, a robust safety culture fosters proactive safety behaviors among workers, significantly reducing accidents and enhancing safety outcomes. Implementing TSM as a continuous improvement approach effectively creates an environment emphasizing worker safety, well-being, and operational effectiveness. The research empirically validates a comprehensive and integrated safety management model using SEM-PLS, providing practical recommendations specifically designed to enhance construction safety performance in developing countries. These insights assist industry practitioners in achieving sustainable safety management, reducing workplace incidents, and striving toward zero fatalities.